My wife is missing - Palmer, Daniel, 1962- (St. Martin's Press, 2022)
"When a woman disappears with her two children, one husband will do anything to find them--even confront the secrets of his own past--in D. J. Palmer's My Wife Is Missing, a twisty thriller from the author of The New Husband.."--